Management of enteroatmospheric fistula with negative pressure wound therapy in open abdomen treatment: a multicentre observational study. Issue 1 (22nd March 2016) - Bobkiewicz, Adam; Walczak, Dominik; Smoliński, Szymon; Kasprzyk, Tomasz; Studniarek, Adam; Borejsza‐Wysocki, Maciej; Ratajczak, Andrzej; Marciniak, Ryszard; Drews, Michal; Banasiewicz, Tomasz
Abstract: The management of enteroatmospheric fistula (EAF) in open abdomen (OA) therapy is challenging and associated with a high mortality rate. The introduction of negative pressure wound therapy (NPWT) in open abdomen management significantly improved the healing process and increased spontaneous fistula closure. Retrospectively, we analysed 16 patients with a total of 31 enteroatmospheric fistulas in open abdomen management who were treated using NPWT in four referral centres between 2004 and 2014. EAFs were diagnosed based on clinical examination and confirmed with imaging studies and classified into low (<200 ml/day), moderate (200–500 ml/day) and high (>500 ml/day) output fistulas. The study group consisted of five women and 11 men with the mean age of 52·6 years [standard deviation (SD) 11·9]. Since open abdomen management was implemented, the mean number of re‐surgeries was 3·7 (SD 2·2). There were 24 EAFs located in the small bowel, while four were located in the colon. In three patients, EAF occurred at the anastomotic site. Thirteen fistulas were classified as low output (41·9%), two as moderate (6·5%) and 16 as high output fistulas (51·6%). The overall closure rate was 61·3%, with a mean time of 46·7 days (SD 43·4). In the remaining patients in whom fistula closure was not achieved ( n = 12), a protruding mucosa was present. Analysing the cycle of negative pressure therapy, we surprisingly found that the spontaneous closure rate was 70% (7 of 10 EAFs) using intermittent setting of negative pressure, whereas in the group of patients treated with continuous pressure, 57% of EAFs closed spontaneously (12 of 21 EAFs). The mean number of NPWT dressing was 9 (SD 3·3; range 4–16). In two patients, we observed new fistulas that appeared during NPWT. Three patients died during therapy as a result of multi‐organ failure. NPWT is a safe and efficient method characterised by a high spontaneous closure rate. However, in patients with mucosal protrusion of the EAFs, spontaneous closure appears to be impossible to achieve.